Social Behaviour of Organization and Employee: Verification of Questionnaire Subscales (Laisvalaikio tyrimai, 2018)
Theoretical substantiation. Lithuania, as an EU member contributing to the Lisbon strategy, aims at building a competitive and dynamic knowledge-based economy, grounded on sustainable economic development, harmonious relations between business, government and civil society. It has approved CSR development vision and development as well as implementation of its priority areas (Astromskiene, Adamoniene, 2009). Social responsibility of the organization is also integrally linked with the organization’s management culture represented by the criteria such as scientific knowledge management, the ability to apply leadership activities, perception of its own role in organizational and social structures, the organization of processes, personal culture and leadership. These are the factors which provide conditions for socially responsible, environmentally sustainable organizational behavior (Andriukaitiene, 2013). According to Z. Simanaviciene, A. Simanavicius and R. Kovaliov (2012), companies that decide to implement the concept of corporate social responsibility first need to define the priority of the area of corporate social responsibility: social responsibility to employees, social responsibility to the local community, social responsibility to the environment and expansion of the company’s value. According to the authors, companies implementing the company’s social responsibility (hereinafter CSR) have to understand that only innovative, high-quality producing and the best consumer-oriented companies can expect to increase their competitiveness and market value after implementing CSR, in particular regarding the positive attitude of the population and willingness to buy their products. V. Juscius and A. Sneideriene (2013) highlight that CSR practice helps to obtain “the public license to operate”, take into account environmental and social issues, create success measurement tools, enhance the brand, improve the company’s financial activities, attract and retain the best employees, increase productivity, improve the quality of goods and services, avoid legal violations, raise capital, avoid public discontent. According to R. Ciegis and R. Norkute (2012), larger organizations uniting more employees as well as providing their goods or services to a greater consumer market are interested in and aim to implement company’s social responsibility. The object of the survey was the reliability of the questionnaire subscales. The aim of study was to verify the organization’s and the employee’s social behaviour questionnaire subscales and their methodological characteristics. The following research objectives were set to achieve the aim: 1) to discuss theoretical aspects of the corporate social responsibility; 2) to validate the reliability of scales and their methodological characteristics; 3) to compare the methodological characteristics of the questionnaire scales Methods Scientific literature analysis and questionnaire survey methods were used. These methods were used for empirical data processing: factorization (primary and secondary), psychometric characteristics for the determination of the reliability of scales. The study sample consisted of 1717 respondents representing all layers of the organization’s staff according to the positions. The survey was conducted in two industrial company groups with 1915 employees in total (1030 and 885 employees) during the study period. The survey nature and terms were combined with the group of companies’ senior management. The empirical study was conducted using article author’s developed questionnaire. The survey carried out in July – August of 2013. The study data was processed using SPSS (Statistical Package for the Social Sciences) programme (Version 21). Findings. Results of this study are one of the constituent parts of the research “Establishment of management culture level in order to implement the concept of a socially responsible company”. Only the methodological characteristics of the social responsibility unit scales of the questionnaire are provided in this article. The study results confirmed that the organization’s social behaviour and employees’ social behaviour scales can be used separately from the management culture block in the questionnaire. Both social responsibility scales matched reliability and validation requirements and no significant differences between the quality characteristics of these scales were observed. The calculations show that the questionnaire is adequate to diagnose the company’s readiness to become socially responsible.Keywords: organization’s social behaviour, employees’ social behaviour, social responsibility, corporate social responsibility.